VD_FINDINFO 30/2013/SNR vom 1. Mai 2013 - VD Tribunal cantonal (2013)
TRANSFERT DES ACTIONS, VENTE, ERREUR ESSENTIELLE, DOLVICE DU CONSENTEMENT, COMPENSATION DE CRÉANCES | 120 CO, 18 al. 1 CO, 18 CO, 184 CO, 23 CO, 24 al. 1 ch. 4 CO, 28 CO, 31 CO, 530 CO, 544 al. 3 CO